Water productivity at two sowing dates of simple white grain maize hybrids (Research, Society and Development, 2024)
In Mexico, maize stands out for its economic, food and cultural importance. Since ancient times, attempts have been made to increase maize grain yields with different alternatives, including hybridization. Currently, maize hybridization offers great advantages since from the first simple hybrids it is possible to evaluate important variables such as water productivity.  The present work was carried out under field conditions in southern Sonora, in two sowing seasons: December 2022- May 2023 (SD 1) and April-August 2023 (SD 2). The research aimed to evaluate the effect of two sowing dates (SD) on phenology, water requirements, water productivity and grain yield. Three single white grain hybrids (L5 X L7; L1 X L2; L2 X L7) obtained from a dialelic design were evaluated. Phenophase occurrence time, irrigation time and interval, total water volume, evapotranspiration, grain yield and water productivity were the evaluated variables. The results showed that in SD 2 significantly reduced the time of occurrence of phenophases in all hybrids due to the effect of temperature. Irrigation time was significantly shorter in SD 2 compared to SD 1. Similarly, the irrigation interval decreased in SD 2 compared to SD 1 with a significant increase in the irrigation lamina. It was necessary to apply two more irrigations to achieve grain filling. Water productivity showed highly significant differences between hybrids and between sowing dates. The simple hybrid L5 X L7 showed better agronomic performance on both sowing dates, demonstrating tolerance to the increase in temperature on SD 2.